Extensive Reading (ER) Practices and the Development of Language Fluency - Resky - Januarty (Bina Nusantara University, 2018)
This research aimed at investigating the Extensive Reading (ER) practices of the students and the development of language fluency. The design of the research was a qualitative study using purposive sampling technique. The data were collected by conducting interview and distributing questionnaire to 20 postgraduate students in Sebelas Maret University, Surakarta, Indonesia. Furthermore, the research revealed some findings on the types of reading materials preferred, reasons and benefits of reading, the effect of the extensive reading practices for the development of language fluency and academic achievement. The results indicate that students prefer the enjoyable reading as their reading sources. Moreover, the books suggested by the teachers to read also become their favorite materials because they obtain some advantages especially in developing language fluency. The finding also implies that extensive reading practices also affect the students’ academic achievement.